Political life of Tevrizsky district of Omsk region: 1996–2012 - O. A. Kiryas (Омский научный вестник: Серия "Общество. История. Современность")
The article presents the reconstruction of the political events of 1992–2012: the elections of the President and the state Duma of the Russian Federation reflected in the district periodic press. The author reveals the features and role of the district press in shaping the political choice of citizens of the district. Based on the materials of the district press, the author presents a political picture of the time, its gradual change and transformation